Request to visit steel fabrication factory and probable paint factory in China by the team of Brac University new campus project (BUNCP) - Brac University (2023)
This record consists of general correspondence regarding the request to visit Steel fabrication factory and probable paint factory in China by the team of Brac University new campus project (BUNCP) of BRACU new campus project site.